Promoting socially responsible business at enterprise level: theoretical approach - Valackienė, Asta; Micevičienė, Diana (Journal of Business Economics and Management, 2014)
The paper highlights theoretical construct of the new methodological approach presenting the interaction between the corporate social responsibility and the performance of the sustainable enterprise, through the introduction of the methodological framework of the diagnosis of corporate social responsibility motivations at the level of a firm seeking to sustain. Acting without knowing all (or at least enough) the answers may mean that we purposely shift our focus to those areas where possible solutions do not emerge. However, entrepreneurship as a phenomenon entailing risk and high levels in daily activities is an engine by profit-seeking motives. It shows the complexity of the scientific research object that brings meaningful input into the analysis of the promotion of socially responsible business. This paper aims at discussing and presenting critical reviews of enterprise’s commitment to corporate social responsibility with emphasis on methodological positions in its promotion. This implicates a shift from the pure stakeholder perspective of maximizing profits thought introduction of enterprise – level interventions in promoting socially responsible business. First published online: 02 Oct 2013